A numerical model for earthquake-induced hydrodynamic forces and wave forces on inclined circular cylinder. (1st July 2020) - Wang, Piguang; Wang, Xiaojing; Zhao, Mi; Cheng, Xinglei; Du, Xiuli
Abstract: An efficient numerical model is presented to calculate the earthquake-induced hydrodynamic forces and wave forces on an inclined circular cylinder with arbitrary angle to the seabed. A finite water domain close to the cylinder is discretized into conventional three-dimensional finite elements. A cylindrical absorbing boundary is used to simulate the remaining infinite water domain. According to the boundary conditions, the exact solution of the absorbing boundary condition is derived by using separation variable method in the cylindrical coordinate system. A coupled equation is obtained by adding the impedance matrix of infinite domain to that of finite domain. The proposed models are verified using the analytical solutions of the earthquake-induced hydrodynamic forces and wave forces on a vertical circular cylinder. The wave forces and earthquake-induced hydrodynamic forces on inclined circular cylinders are furtherly investigated. Finally, the added mass for an inclined circular cylinder vibrating in water is studied and a simplified formula of the added mass is also presented in the present study. Highlights: The finite element model for solving the hydrodynamic forces and wave forces on an inclined circular cylinder is presented. The cylindrical exact absorbing boundary condition for simulating the unbounded fluid domain is derived. The wave and earthquake-induced forces on an inclined circular cylinders are investigated. The simplified formulas for earthquake-induced hydrodynamic forces on an inclined circular cylinder are given.